2003
DOI: 10.1016/s0890-6955(03)00037-3
|View full text |Cite
|
Sign up to set email alerts
|

An experimental technique for the measurement of temperature fields for the orthogonal cutting in high speed machining

Abstract: Cutting temperature and heat generated at the tool-chip interface during high speed machining operations have been recognized as major factors that influence tool performance and workpiece geometry or properties. This paper presents an experimental setup able to determine the temperature field in the cutting zone, during an orthogonal machining operation with 42 CrMo 4 steel. The machining was performed with a gas gun, using standard carbide tools TiCN coated and for cutting speeds up to 50 ms -1 . The techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(68 citation statements)
references
References 25 publications
4
56
2
2
Order By: Relevance
“…This indicates that the TiN coating on the multi-layer coated tool produces higher cutting forces at low cutting speeds, and lower cutting forces at high cutting speeds. A similar result was reported by Suter et al [14].…”
Section: Analysis Of Cutting Force Feed Force and Radial Forcesupporting
confidence: 91%
See 1 more Smart Citation
“…This indicates that the TiN coating on the multi-layer coated tool produces higher cutting forces at low cutting speeds, and lower cutting forces at high cutting speeds. A similar result was reported by Suter et al [14].…”
Section: Analysis Of Cutting Force Feed Force and Radial Forcesupporting
confidence: 91%
“…Other researcher, Sutter et al [14] have reported similar results. The decrease in cutting force (F c ) with increased cutting speed was due to the increase in cutting temperature at the shear zone.…”
Section: Analysis Of Cutting Force Feed Force and Radial Forcesupporting
confidence: 60%
“…Knowledge of the cutting forces is needed for the estimation of power requirements, the adequately rigid design of machine tool elements, tool-holders, and fixtures, for vibration free operations [7][8]. Sutter et al [9] studied the effects of the cutting speed and depth of cut on the temperature profile of the chip during an orthogonal machining of 42 CrMo 4 steel using standard carbide tools TiCN coated, it was observed that temperature at the chip increases with the increase in both cutting speed and the depth of cut. Abukhshim et al [10] assessed the magnitude of heat flow during turning operation of AISI 4140 high strength alloy steel using Finite element analysis [FEA].…”
Section: Introductionmentioning
confidence: 99%
“…Sutter et al [8] presented an experimental setup which is able to determine the temperature field in the cutting zone during an orthogonal machining operation, performed with a gas gun developed on the principle of pyrometry in the visible spectral range by using an intensified CCD camera.…”
Section: Introductionmentioning
confidence: 99%